Sentimen Analisis Terkait Lockdown pada Sosial Media Twitter - Muhammad Dwison Alizah; Arifin Nugroho; Ummu Radiyah; Windu Gata (Universitas Bina Sarana Informatika, 2020)
Abstract: Covid-19 has been set as a Pandemic by the World Health Organization (WHO). The very large impact and the infection that is fast enough are the reasons for making Covid-19 as a pandemic and efforts to overcome. One anticipation that can be done is to do lockdown. Making the decision to carry out a lockdown is intended to reduce the spread that occurs. Lockdown is certainly not a 100% good solution for all of individual. There are individual who agree that the lockdown will be implemented, also there are those who think that the lockdown is better not to be carried out considering the negative impacts that can occur. Therefore in this study will be presented the predictive modeling for sentiment analysis related to